2016
DOI: 10.3892/etm.2016.3135
|View full text |Cite
|
Sign up to set email alerts
|

Fibroscan improves the diagnosis sensitivity of liver fibrosis in patients with chronic hepatitis B

Abstract: The aim of the present study was to investigate the diagnostic accuracy of Fibroscan for liver fibrosis in patients with chronic hepatitis B (CHB) with alanine aminotransferase (ALT) levels <2 times the upper normal limit. A total of 263 consecutive patients with CHB and ALT levels <2 times the upper normal limit were enrolled in the present study. Liver biopsies and liver stiffness measurements (LSM) were conducted. Receiver operating characteristic (ROC) analysis was used to determine the predictive ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…The invasiveness of liver puncture, the limitation of the specimen, and the poor patient compliance have restricted the application of LB, which has led to the development of noninvasive methods such as FIB-4[ 13 ] and aspartate aminotransferase (AST)-to-platelet ratio index (APRI)[ 14 ] for evaluating fibrosis in patients with chronic HBV infection. Liver stiffness measurement (LSM) using transient elastography (FibroScan) has been widely used in the diagnosis of chronic liver fibrosis[ 15 , 16 ]. However, the diagnostic value of FIB-4, APRI, and LSM in patients with HBV infection with PNALT is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The invasiveness of liver puncture, the limitation of the specimen, and the poor patient compliance have restricted the application of LB, which has led to the development of noninvasive methods such as FIB-4[ 13 ] and aspartate aminotransferase (AST)-to-platelet ratio index (APRI)[ 14 ] for evaluating fibrosis in patients with chronic HBV infection. Liver stiffness measurement (LSM) using transient elastography (FibroScan) has been widely used in the diagnosis of chronic liver fibrosis[ 15 , 16 ]. However, the diagnostic value of FIB-4, APRI, and LSM in patients with HBV infection with PNALT is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Liver biopsy whilst evident as the gold standard of liver fibrosis is difficult, invasive and costly. [34] Liver stiffness measurement (LSM) using fibroscan is increasingly being used to assess disease severity. [35] This procedure can help to enhance HCV assessment, reduce treatment barriers, triage patients and target therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed the utility of TE for the diagnosis of fibrosis in 263 HBV patients with ALT levels <2× upper limit of normal (ULN), particularly in those with at least significant underlying fibrosis. LS value was also found to correlate significantly with both liver fibrosis and necroinflammatory activity on biopsy, a consideration for the interpretation of TE measurements (104). Some authors have suggested that TE cut-offs should incorporate ALT levels which fluctuate with inflammation in HBV, and TE may be particularly useful HbeAg-negative patients with normal LFTs to guide the need for biopsy of treatment (105).…”
Section: Liver Stiffness Measurement: Transient Elastography (Te)-fibmentioning
confidence: 99%